Observations of truck-bicycle encounters: A case study of conflicts and behaviour in Trondheim, Norway. (January 2019) - Pokorny, Petr; Pitera, Kelly
Highlights: Within 340 h of recordings, 979 encounters and 31 conflicts were detected. Behavioural analysis were conducted in conjunction with conflict analysis. Event-based approach to exposure was used to compare risk of sites and encounters. Right turning encounters involved the highest share of conflicts. Several forms of risk awareness between cyclists and truck drivers were observed.